An Evaluation of Women and the Ideological Interest of the Integrated Islamic School - Nurus Shalihin; M Yusuf; Mufti Ulil Amri (Jurnal Penelitian, 2022)
This study aims to analyze the phenomenon of female teachers as mediators in the ideological value transmission by Integrated Islamic Schools in Early Childhood Education institutions. Data were collected using two different techniques, namely questionnaires and in-depth interviews. A total of 43 respondents were selected as the study samples from 11 Integrated Islamic Schools in Early Childhood Education. The result showed that the Integrated Islamic Schools had taken advantage of the gender equality issue promoted by globalization in placing women as educational actors. It has also exploited the conceptions and stereotypes of women as actors with sufficient potential to deal with children in Early Childhood Education institutions. Conclusively, the Integrated Islamic School has empowered women to serve as strategic mediators who can be exploited as a catalyst for instilling ideological values through meeting spaces in each Integrated Islamic School.